FORGOTTEN OR INCLUDED? DISABLED CHILDREN’S ACCESS TO PRIMARY EDUCATION IN CAMEROON (African Disability Rights Yearbook, 2021)
Cameroon is party to international and regional instruments providing for the right to education, in particular compulsory and free primary education. This article examines the right to inclusive primary education in Cameroon. It investigates the extent to which children with disabilities are included in primary schools. After a clarification of the concept of inclusive education, this article argues that children with disabilities are forgotten under the Cameroonian dispositions relating to access to primary education. This is a blatant violation of the right to universal access to primary education. Therefore, this article calls upon the Cameroonian government to enact laws and policies to implement a universal learning design (ULD) which entails the development of a curriculum and teachers training to meet various needs in a classroom.
Keywords: Cameroon; right to education; children with disabilities; primary schools; universal learning design